2009
DOI: 10.1186/1471-2202-10-155
|View full text |Cite
|
Sign up to set email alerts
|

A case of polymicrogyria in macaque monkey: impact on anatomy and function of the motor system

Abstract: Background: Polymicrogyria is a malformation of the cerebral cortex often resulting in epilepsy or mental retardation. It remains unclear whether this pathology affects the structure and function of the corticospinal (CS) system. The anatomy and histology of the brain of one macaque monkey exhibiting a spontaneous polymicrogyria (PMG monkey) were examined and compared to the brain of normal monkeys. The CS tract was labelled by injecting a neuronal tracer (BDA) unilaterally in a region where low intensity elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…All measures were taken to minimize pain and constraints on the animals, and their number was also kept as low as possible, in particular using the same cases (namely BDA injections in various motor cortical areas) to study distinct connection/projection systems (Rouiller et al, 1994(Rouiller et al, , 1996(Rouiller et al, , 1998(Rouiller et al, , 1999Liu et al, 2002;Tann e-Gari epy et al, 2002a,b;Freund et al, 2007;Schmidlin et al, 2009;Fregosi et al, 2017;Innocenti et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…All measures were taken to minimize pain and constraints on the animals, and their number was also kept as low as possible, in particular using the same cases (namely BDA injections in various motor cortical areas) to study distinct connection/projection systems (Rouiller et al, 1994(Rouiller et al, , 1996(Rouiller et al, , 1998(Rouiller et al, , 1999Liu et al, 2002;Tann e-Gari epy et al, 2002a,b;Freund et al, 2007;Schmidlin et al, 2009;Fregosi et al, 2017;Innocenti et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…It was suggested that ischemic infarction or hemorrhage near the time of birth caused the neuroanatomic deficits in this animal. In some colonies of Japanese monkeys, myeloencephalitis with Streptococcus infection (Lair et al 1996), polymicrogyria (Schmidlin et al 2009), neuropathy due to coyotillo intoxication (Joiner et al 1975), multifocal malacia due to Baylisascaris larva migrans (Sato et al 2005), and cerebellar cortical atrophy (Sanford and Mehren 1979) have been reported.…”
Section: Discussionmentioning
confidence: 99%